Autism and specific language impairment: categorical distinction or continuum? - Bishop, D (2003)
Traditionally, autism and specific language impairment (SLI) are regarded as distinct disorders, with differential diagnosis hinging on two features. First, in SLI one sees isolated language impairments in the context of otherwise normal development, whereas in autism a triad of impairments is seen, affecting communication, social interaction and behavioural repertoire. Second, there are different communication problems in these two conditions. Children with SLI have particular difficulty with structural aspects of language (phonology and syntax). In contrast, abnormal use of language (pragmatics) is the most striking feature of autism. However, recently, this conventional view has been challenged on three counts. First, children with autism have structural language impairments similar to those in SLI. Second, some children have symptorns intermediate between autism and SLI. Third, there is a high rate of language impairments in relatives of people with autism, suggesting aetiological continuities between SLI and autism. One interpretation of these findings is to regard autism as 'SLI plus', i.e. to assume that the only factor differetiating the disorders is the n presence of additional impairments in autism. It is suggested that a more plausible interpretation is to regard structural and pragmatic language impairments as correlated but separable consequences of common underlying risk factors.